Aesculus indica: an updated review on its pharmacognosy, phytochemistry and pharmacological profile. Issue 1 (31st December 2022) - Yadav, Neha; Singh, Aakash Partap; Rana, Avtar Chand; Kumar, Sunil; Kaur, Prabhjeet; Singh, Jitender; Jangra, Ashok; Kumar, Dinesh
ABSTRACT: Aesculus indica Wall. Ex Camb. Hook, a member of Hippocastanaceae family, is widely distributed in the low temperature region of the world. Various parts of this plant are enriched with bioactive molecules and used to treat a variety of illness such as abdominal colic, thrombosis, hemorrhoids, diabetes, rheumatism and skin diseases. All the information related to this plant was collected from different treatise and reference books, and databases like PubMed, Scopus, Science Direct, Web of Science, Google Scholar etc. In this review, the pharmacognosy, phytochemistry and pharmacological properties of this plant and its patented formulations have been thoroughly discussed in order to provide a comprehensive and updated information for the scientists or researchers working on natural products. GRAPHICAL ABSTRACT: uf0001